Finite Element Simulation and Analysis of Magnesium/Aluminum Composite Tube with Stagger Spinning - Ning SHI; Wenxian WANG; Tingting ZHANG; Hongsheng CHEN (Taiyuan Ligong Daxue xuebao, 2021)
In order to explore the deformation behavior of materials during the preparation of magnesium/aluminum composite pipes by offset spinning, and the influence of various factors on the formability of composite tubes, in this study, the effects of parameters such as spinning temperature, thickness reduction, and feed ratio on the coordination of deformation of the inner and outer tubes were analyzed by using finite element simulation. The results show that improving spinning temperature and reduction rate is helpful to improve the deformation coordination and forming quality of inner and outer tubes, and increasing the feed ratio appropriately can improve the surface forming precision of composite tubes. When the spinning temperature is 350 ℃, the reduction is 30%, and the feed ratio is 1 mm/r, the forming quality of the composite tubes is better. The radial equivalent stress of the composite tubes shows a gradient distribution, which causes the discontinuity of the plastic strain of the inner and outer tubes. Reliable machining intervals were obtained through numerical simulation, which provides a theoretical basis for actual forming.